STUDI PENGARUH LAMA WAKTU PENGADUKAN TERHADAP KUAT TEKAN BETON - Puspitasari, Ira; Upin, La Ode (Fakultas Teknik Universitas Khairun, 2024)
In obtaining good concrete quality according to the requirements, sometimes problems arise including urgent and limited time to immediately accelerate the work, the distance traveled to transport concrete mixture from the mixing machine to the place of work, the influence of temperature and weather. This study aims to determine the effect of mixing time on the compressive strength of concrete. The length of stirring time in question is the amount of time used to mix the concrete mixture in minutes, which is calculated after all the ingredients are put into the mixing drum (molen). The mixing time is varied as many as 3 different times, namely 10, 20 and 30 minutes. This test was carried out at a maintenance age of 28 days, with a cylindrical test specimen dimension of 15 cm x 30 cm, each comparison was made with 3 test pieces where the total number was 9 test pieces. The compressive strength of concrete results from the length of mixing time between 10, 20, and 30 minutes. In concrete with a mixing time of 10 minutes, the highest compressive strength value is 13.01 MPa, while in the mixing time of 20 minutes, the highest compressive strength value is 15.48 MPa, and at the mixing time of 30 minutes, the highest compressive strength value is 15.48 MPa. The highest concrete content weight value is in concrete with 30-minute stirring, which is 2.30 gr/cm3, in 10-minute stirring the highest content weight value is 2.29 gr/cm3 and in 20-minute casting the highest content weight value is 2.29 gr/cm3.Keywords: Mixing time, Strong compressive,Content Weight